Libyan Students’ Syntactic and Semantic Problems in Using Phrasal Verbs to Write English Texts - Salem Mohammed, Abdelraouf; Mujiyanto, Januarius; Faridi, Abdurrahman (Universitas Negeri Semarang, 2020)
This study aimed to explore the existence of syntactic problems and semantic problems and to explain the relation of syntactic problems to semantic problems among Libyan students in using phrasal verbs during writing English texts. The participants in this study were ten Libyan students studying in three Universities in Semarang, Central Java, Indonesia. The ten participants were from different majors of Master and Doctoral degrees. They can use English language in their study so they have a basic knowledge of English. The data were ten English which taken by Libyan students as previous papers. In this study, the researcher used a descriptive qualitative method to analyze the data. The results showed that Libyan students have three problems related to adverb insertion, particle placement and fronting particle and they have semantic problems in understanding the meanings in the semantic classes of phrasal verbs and semantic (non-)compositionality. Finally, the researcher found out that the syntactic behaviour of particles depends on semantic (non-)compositionality.